2010
DOI: 10.1097/wnf.0b013e3181d1e133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Valproate, Carbamazepine, and Levetiracetam on the Antioxidant and Oxidant Systems in Epileptic Patients and Their Clinical Importance

Abstract: Oxidative stress is seen in each of the AEDs after the first 2 months. There was no dominance of the monotherapy over the polytherapy, except for the VPA-LEV combination. None of the patients' characteristic features were related to oxidative damage, except for the duration of the epilepsy and the AED therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 13 publications
2
39
0
Order By: Relevance
“…Lower TAC [86] and GSH [98] in plasma, and GPX and CAT in erythrocytes were also observed [92]. In accordance with its pro-oxidative action, decreased SOD [92] and increased 8-OHdG [96] and nitrite/nitrate in erythrocytes were also observed. However, there are also studies which do not confirm CBZ pro-oxidative action [83, 86, 91, 95] and even studies with anti-oxidative action [88, 93, 99].…”
Section: Antiepileptic Drug Therapy and Oxidative Stressmentioning
confidence: 91%
See 1 more Smart Citation
“…Lower TAC [86] and GSH [98] in plasma, and GPX and CAT in erythrocytes were also observed [92]. In accordance with its pro-oxidative action, decreased SOD [92] and increased 8-OHdG [96] and nitrite/nitrate in erythrocytes were also observed. However, there are also studies which do not confirm CBZ pro-oxidative action [83, 86, 91, 95] and even studies with anti-oxidative action [88, 93, 99].…”
Section: Antiepileptic Drug Therapy and Oxidative Stressmentioning
confidence: 91%
“…Erythrocyte GPX [91, 92], GR [93] and serum Se [94], uric acid and albumin [80], which are considered endogenous enzymatic and non-enzymatic antioxidant molecules, were found to be reduced in children and adults treated with VPA. Furthermore, in studies in patients with epilepsy, treated with VPA, increased levels of oxidative macromolecular damage markers, such as MDA [76, 86, 90, 91] and 15F-2t-isoP [95], which are markers of enhanced lipid peroxidation and increased levels of 8-OHdG [90, 96], which is a marker of nucleic acid damage, were observed. Similarly, enhanced lipid peroxidation [80] and decreased SOD and GPX [92] was seen in studies with phenobarbital.…”
Section: Antiepileptic Drug Therapy and Oxidative Stressmentioning
confidence: 99%
“…Studies on the effect of AEDs on prooxidative/antioxidant balance in patients with epilepsy have, so far, mainly focused on valproic acid and carbamazepine treatments and their effect on the lipid peroxidation process and antioxidant defense mechanisms (1,11,22,23). Interestingly, the extent of protein oxidative damage has not been evaluated, while DNA oxidative damage has only been examined in children receiving valproic acid therapy and recently, in one study, on adult patients receiving valproic acid, carbamazepine and levetiracetam (16,24). Furthermore, data on lamotrigine effects on oxidative stress in patients with epilepsy are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…*P \ 0.05 the oxidative stress system of epilepsy patients [31][32][33], leading to increased risk of atherosclerosis in children and adults who are taking antiepileptic treatment [14,15]. In epileptic children who are treated with AEDs, there is an increase in the oxidative modification of low-density lipoprotein cholesterol (LDL-C), an important factor responsible for atherosclerosis [34,35]. Varoglu et al (2010) reported significantly lower serum paraoxonase and ARE activities of PON1, an antioxidant enzyme with three activities of paraoxonase (PON1), ARE, and dyazoxonase that can destroy active lipids in mildly oxidized LDL-C (ox-LDL) and, thus, prevent the induction of inflammatory response [36].…”
Section: Discussionmentioning
confidence: 99%